Pengembangan Madrasah Unggulan Di Madrasah Diniyah Miftahul Huda Sumurpanggang Margadana Tegal Jawa Tengah - Syahri, Akhmad (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2016)
The development of madrasah seed can not be treated partially or half-and-half but requires thinking the development of complete and comprehensive as well as measures and efforts are visible, flexible, and credible, especially when faced with the national development policy in education with a vision realization of the education system as an institution strong social and authoritative to empower all citizens of Indonesia to develop into a human quality, so capable and pro-active answer the challenges of the times are always changing (see an explanation of Law No. 20/2003 on the National Education System). Plus the era of globalization has had a wide impact on many aspects of life, including the demands for quality in the organization of education. In this era demands every field of Human Resources (HR) quality of high caliber and reliability, so competition especially concerning human resources is very tight. To meet this demand, the improvement and development of education provision in each madrasah system continuously needs to be done in line with the dynamic development of science and technology (Science and Technology) and the dynamic changes in society itself. Strengthening the institutions of excellence through how to build ideals and a strong academic culture that lead to superior output and good as-expected madrasah in this age of globalization. Keywords: development of education, madrassa, an Islamic education